Impact of green training on environmental performance through mediating role of competencies and motivation - Yafi, E.; Tehseen, Shehnaz *; Haider, S. A. (MDPI, 2021)
This work aims to examine the impact of green training on green environmental performance through the mediating role of green competencies and motivation on the adoption of green human resource management. The convenience sampling technique was employed to collect data through an online survey undertaken at public and private universities in Malaysia. The analyses were conducted using the Statistical Package for the Social Sciences (SPSS) v.25 and Smart PLS v.3 software, with the aim of testing the predefined hypotheses. It was revealed that green training has a significant impact on green environmental performance, and all six dimensions of green competencies, namely, skills, abilities, knowledge, behavior, attitude and awareness, were also green motivations. Both green competencies and motivations positively and significantly mediated the relationship between green training and environmental performance.